2022
DOI: 10.1007/s12529-022-10076-8
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Fidelity of Telephone Motivational Interviewing On Physical Activity, Fruit Intake, and Vegetable Consumption in Dutch Outpatients With and Without Hypertension

Abstract: Background In theory, Motivational Interviewing (MI) fidelity should be associated with client outcomes. Nevertheless, this fidelity-effectiveness association is rarely investigated. This study evaluated the extent to which Telephone Motivational Interviewing (TMI) fidelity is associated with change in self-reported physical activity (PA), fruit intake, and vegetable consumption. Method Adults in primary care (45–70 years) participated in a study that comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…34 An intervention study using Telephone MI conducted among the Dutch population found a significant relationship between the percentage of MI adherent expressions and change in the level of PA from baseline to 47-week follow-up, with a small effect size (p<0.05). 37…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 An intervention study using Telephone MI conducted among the Dutch population found a significant relationship between the percentage of MI adherent expressions and change in the level of PA from baseline to 47-week follow-up, with a small effect size (p<0.05). 37…”
Section: Discussionmentioning
confidence: 99%
“…However, the research did not identify a significant correlation between the utilization of motivational interviewing and vegetable intake. 37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of technology, such as mobile, telephone, or web-based approaches in MI, has been demonstrated to provide satisfactory outcomes. 36 , 37 The investigators of the BEHOLD-16 RCT have pilot tested the feasibility and acceptability of a 16-week telephone-based combined positive psychology-MI intervention to promote PA in patients with T2DM. An average of 11 (of 14) sessions were completed by the participants, and a satisfactory composite mean score of ease/utility (8.6/10) was found.…”
Section: Healthy Relationshipsmentioning
confidence: 99%